Komunikasi Efektif Guru dalam Meningkatkan Kemampuan Belajar pada Anak Usia Dini di KB Putri Fadilla - Faridah Faridah; Muslim Muslim; Syahru Ramadhan (Yayasan Assyifa Assyaka, 2025)
The background of this research is based on the importance of good communication between teachers and children in the learning process, which can affect children's cognitive, social and emotional development. Given the rapid development of early childhood, effective communication is the main key in creating a supportive learning environment. The type of research used is descriptive qualitative research with a case study approach. Data collection techniques were carried out through observation, interviews and documentation. The data sources in this study are teachers, children and parents who are directly involved in learning activities at KB Putri Fadila. The data analysis technique used is qualitative analysis with the steps of data collection, data reduction, data presentation, and conclusion drawing. The results showed that various forms of effective communication applied by teachers, such as interactive learning through educational games, interactive stories with visual media, learning through music and movement, and technology integration, succeeded in improving children's learning abilities. These activities not only make learning more interesting, but also strengthen children's social, motor and cognitive skills. This study concludes that effective teacher communication at KB Putri Fadila has a positive impact on improving the quality of learning for early childhood.